Abstract Or118: Transcription Factor Gene Therapy for Treatment of Junctional Bradycardia in a Porcine Model of Complete Atrioventricular Block Following His Bundle Ablation - Ramirez, Rafael; Bergman, Samuel; Masri, Jamal; Weltz, Alexander; Kumar, Naman; de la Uz, Caridad; Kolandaivelu, Aravindan; Barth, Andreas; Barcelon, Bernadette; Fan, Jinqi; Cho, Hee Cheol (Circulation research, 2024)
Background: Pacemaker implantation is standard treatment for patients with complete atrioventricular (AV) block. However, contraindications for device implantations create a need for alternative non-hardware cardiac pacing solutions. We developed a porcine model of complete heart block with junctional bradycardia to test a novel transcription factor-based gene therapy consisting of Tbx18, Shox2 and Tbx3 (TST). Somatic reprogramming of ventricular cardiomyocytes by TST induces pacemaker-like activity and provides biological pacing in vitro. Methods: Eight domestic swine (Yorkshire/Landrace) received catheter ablation of the AV node/His Bundle resulting in complete AV block, confirmed by dissociation of P and R waves on ECG. An implanted device pacemaker (VVI mode) maintained cardiac output during occurrences of junctional bradycardia below 50 bpm. Telemetric 3-lead ECG was recorded continuously. Subjects received TST gene therapy or control gene (GFP) via catheter-based intramuscular injection into the high right ventricular septum. Pacemaker usage and ECG were continuously monitored for 8 weeks. Results: Following AV node ablation, junctional escape rhythm decelerated into junctional bradycardia. After 3 weeks of AV block, 49.9 ± 13.1% of heartbeats were initiated by the device pacemaker. Upon reaching pacemaker dependence of 95% in an average of 27.9 ± 5.5 days, subjects received TST gene therapy or control injection. In subjects receiving TST therapy, daily pacemaker reliance decreased to 50% dependency in an average of 14.7 ± 2.3 days, while in GFP controls, daily pacemaker dependency at 50 bpm remained unchanged at >98% throughout follow-up. In TST-treated subjects, reductions in pacemaker dependence were associated with increases in ventricular rates exceeding 70 bpm. Efficacy of gene therapy waned after about one month; an improvement of >10% pacemaker dependency over two consecutive days was still observed on average 29.0 ± 4.1 days after TST injection. Conclusion: In a porcine model of complete AV block, ventricular junctional escape rhythm decelerated into bradycardia in less than one month. Subsequent gene therapy by TST injection into the high ventricular septum alleviated pacemaker dependency and enhanced heart rate for 29.0 ± 4.1 days. Somatic reprogramming of cardiomyocytes by TST gene delivery may provide a biological pacemaker alternative to hardware device implantation for therapeutic cardiac pacing.